Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

A Moving Target: Matching Graduate Education with Available Careers for Ocean Scientists - Melbourne Briscoe; Deborah Glickson; Susan Roberts; Richard Spinrad; James Yoder (Oceanography, 2016)

E-DECIDER: Using Earth Science Data and Modeling Tools to Develop Decision Support for Earthquake Disaster Response - Margaret T. Glasscoe; Jun Wang; Marlon E. Pierce; Mark R. Yoder; Jay W. Parker; Michael C. Burl; Timothy M. Stough; Robert A. Granat; Andrea Donnellan; John B. Rundle; Yu Ma; Gerald W. Bawden; et al. (Pure and Applied Geophysics, 2015)

Differential expression and ligand binding indicate alternative functions for zebrafish polymeric immunoglobulin receptor (pIgR) and a family of pIgR-like (PIGRL) proteins - Amanda N. Kortum; Ivan Rodriguez-Nunez; Jibing Yang; Juyoung Shim; Donna Runft; Marci L. O’Driscoll; Robert N. Haire; John P. Cannon; Poem M. Turner; Ronda T. Litman; Carol H. Kim; Melody N. Neely; et al. (Immunogenetics, 2014)

Amyloid pathway-based candidate gene analysis of [11C]PiB-PET in the Alzheimer’s Disease Neuroimaging Initiative (ADNI) cohort - Shanker Swaminathan; Li Shen; Shannon L. Risacher; Karmen K. Yoder; John D. West; Sungeun Kim; Kwangsik Nho; Tatiana Foroud; Mark Inlow; Steven G. Potkin; Matthew J. Huentelman; David W. Craig; et al. (Brain Imaging and Behavior, 2012)

Immunoglobulin variable regions in molecules exhibiting characteristics of innate and adaptive immune receptors - Gary W. Litman; John P. Cannon; Larry J. Dishaw; Robert N. Haire; Donna D. Eason; Jeffrey A. Yoder; Jose Hernandez Prada; David A. Ostrov (Immunologic Research, 2007)

A model for pro‐poor wealth creation through small‐plot irrigation and market linkages - John Magistro; Michael Roberts; Steve Haggblade; Fritz Kramer; Paul Polak; Elizabeth Weight; Robert Yoder (Irrigation and Drainage, 2007)
This paper relates the field experience of an international NGO in strengthening linkages between irrigation development and poverty reduction. Poverty Reduction through Irrigation and Smallholder Markets (PRISM) is introduced as a methodology for combining small‐plot irrigation technology with complementary inputs and services to enhance small farmers' ability to participate effectively in markets for high‐value agricultural commodities. Data from field projects in Nepal and India indicate that the PRISM approach can lead to significant additional income for small farmers and other micro and small enterprises in agricultural value chains. Copyright © 2007 John Wiley & Sons, Ltd.

Relationships of Exodontiella , a non‐alysiine, exodont member of the family Braconidae (Insecta, Hymenoptera) - Robert A. Wharton; Matthew J. Yoder; Joseph J. Gillespie; John C. Patton; Rodney L. Honeycutt (Zoologica Scripta, 2006)
The placement of Exodontiella Wharton is re‐examined in light of the discovery of four additional individuals. Genomic DNA was extracted from one of the individuals, the D2 expansion segment of the 28S rRNA gene was sequenced, and the sequence compared to selected taxa within the Braconidae. Based on the molecular data and the morphological study, Exodontiella is formally transferred from the Opiinae to the Gnamptodontinae. The genus and its included species are redescribed.

Creating wealth from groundwater for dollar-a-day farmers: Where the silent revolution and the four revolutions to end rural poverty meet - Paul Polak; Robert Yoder (Hydrogeology Journal, 2006)

Predicted Secondary Structure for 28S and 18S rRNA from Ichneumonoidea (Insecta: Hymenoptera: Apocrita): Impact on Sequence Alignment and Phylogeny Estimation - Joseph J. Gillespie; Matthew J. Yoder; Robert A. Wharton (Journal of Molecular Evolution, 2005)

Putting Together the Big Picture: Remote-Sensing Observations of Ocean Color - James Yoder; Keith Moore; Robert Swift (Oceanography, 2001)

Cloning of two zebrafish cDNAs that share domains with the MHC class II-associated invariant chain - Jeffrey A. Yoder; Robert N. Haire; G. W. Litman (Immunogenetics, 1999)

Hydraulic lift among native plant species in the Mojave Desert - Carolyn K. Yoder; Robert S. Nowak (Plant and Soil, 1999)